DISCOURSE ANALYSIS OF MISS UNIVERSE 2018—2023’s WINNING ANSWERS - Sotyarani Padmarintan; Ni Gusti Ayu Roselani (Universitas Wiralodra, 2024)
This article aims to describe Miss Universe 2018—2023’s winning answers textually and contextually with qualitative descriptive research to see the use of language functions in a Miss Universe Competition. The data for this research are words, phrases, clauses, and sentences from Miss Universe 2018—2023’s winning answers that are collected using listening and note-taking techniques. This research step includes determining the type of discourse, the unit of analysis, and describing data units. This research found that there are 126 grammatical and lexical elements. In the grammatical aspect, there are 54 references, 2 substitutions, 14 ellipsis, and 33 conjunctions. In the lexical aspect, there are 3 synonyms, 2 antonyms, 2 hyponyms, 6 repetitions, 8 collocations, and 2 equivalences. In the contextual aspect, the discourse is discussed in social cognition and social analysis using Teun Van Dijk's theory. As a result, the discourse was influenced by negative events occurring in society, so the content of the discourse focused on Miss Universe 2018—2023's efforts to influence the target audience to be brave in facing that inequality. This discourse also emerged due to two social factors, the power factor with the prestigious status of Miss Universe and the broad international access factor.